INSPECTION AND PROCESSING TECHNIQUES OF ASSESSMENT RESULTS IN LEARNING - Hambali Alman Nasution (UIN Sumatera Utara Medan, 2020)
The purpose of this paper is to determine the technique of examination and processing of assessment results. This research uses a type of library research, namely research that uses various literature sources such as books and journal articles to serve as writing guidelines. This article's results indicate that there are steps that must be carried out in the assessment, namely when examining and processing the assessment results. In the stage of checking the assessment results, correcting the students' answers carefully and thoroughly according to the existing scoring guidelines. The raw scores obtained so that they become more meaningful and must be interpreted based on specific and relevant assessment references and needs, namely by benchmarking reference assessments ( PAP) and norm-referenced assessment (PAN). For example, to determine whether students' scores have met the passing grade predetermined, then use a benchmark reference assessment. Meanwhile, to determine the comparison of students' scores, it uses the norm reference assessment.